Rise in Deaths Due to Fall from Height: A 3-Year Retrospective Study (Medico Legal Update, 2019)
Deaths due to fall from height are the second leading cause of injury-related deaths. The fatalities of theinjuries depend not only on the height of fall but also on the landing position and impact surface. Additionally,diversity of the injuries and the complexity of the patterns involved in these injuries, emphasizes the needfor study in this area. A retrospective autopsy study of deaths due to fall from heights was carried out atthe Department of Forensic Medicine, KIMS Hospital, Bangalore from January 2014 to December 2016.Among the total 1911 cases autopsied during the study period, 90 cases (4.07%) were deaths due to fall fromheight. Maximum number of cases was in the second decade of their lives (36.6%) and was followed bycases in third decade (21.1 %). male to female ratio was 6.5:1. About 41.1% of the cases were constructionworkers, followed by 15.5% students. Fatal height of fall was within 0-20 feet (48.8%) followed by 21-40 feet (44.4%).Amongst the fatal fall, 63.3% of cases succumbed to injuries without treatment. It wasobserved that in 41.1% the impact was on hard surface followed by fall on tiles in 35.5%.Head injury wasthe leading cause of death in 51.1% of the cases. We concluded that fall from heights carry a significantmorbidity and mortality and to decrease the incidence of these deaths, it is important to employ certain vitalstrategies. These include creating awareness amongst workers, increasing parental supervision of toddlersduring their play at heights and psychological counseling for students.